Sustaining human lives through family efforts in organ donation / Farah Salwani Muda@Ismail - Muda@Ismail, Farah Salwani (2020)
Human lives are too precious to waste. Therefore, maximum effort is taken to guard and protect lives of each and every human being on earth. Organ donation, as a miracle in the modern medical world, clearly spells out this concept. Vital organs are supplied from other humans with the intention to allow lives of patients in need, suffering from end stage organ failures to be extended and saved. Malaysia positively supports this kind deed, though unfortunately we still suffer from severe organ shortage problems. This paper will encapsulate a spectrum of knowledge by introducing steps that could possibly help overcome organ shortage in Malaysia, including by eliminating family refusal and introducing a family-witness support system. These suggestions will obviously contribute towards the sustainability of precious human lives.